2007
DOI: 10.1063/1.2740324
|View full text |Cite
|
Sign up to set email alerts
|

Study of SiNx and SiO2 passivation of GaN surfaces

Abstract: Articles you may be interested inStudy of surface leakage current of AlGaN/GaN high electron mobility transistors Appl. Phys. Lett.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 50 publications
3
40
0
1
Order By: Relevance
“…We ran the routine several times, varying surface band bending in the dark from 0.3 V to 0.7 V and surface band bending under illumination from 0 V to 0.05 V. The actual surface band bending for our GaN nanowires is unknown. For nanowire devices measured in the dark, we chose values within the literature range of 0.1 V to 1.1 V. [28][29][30] Surface band bending for illuminated nanowires was much lower. The intention was to reduce the surface band bending to 0 V, but since this could not be confirmed, a range of low values was used.…”
Section: Modelmentioning
confidence: 99%
“…We ran the routine several times, varying surface band bending in the dark from 0.3 V to 0.7 V and surface band bending under illumination from 0 V to 0.05 V. The actual surface band bending for our GaN nanowires is unknown. For nanowire devices measured in the dark, we chose values within the literature range of 0.1 V to 1.1 V. [28][29][30] Surface band bending for illuminated nanowires was much lower. The intention was to reduce the surface band bending to 0 V, but since this could not be confirmed, a range of low values was used.…”
Section: Modelmentioning
confidence: 99%
“…Compared with Device-A, the leakage currents of the PVs with a SARL and a MARL was improved by 39.3% and 95.7%, respectively. Device-C had the lowest leakage current, which may be attributed to the reduction of surface and edge leakage paths due to the MARL (as a passivation layer) and the surface and edge recombination improvement [14][15][16][17]. Because the forward current relies on the amount of recombination in a p-n junction, increasing the recombination increases the forward bias current.…”
Section: Methodsmentioning
confidence: 99%
“…The fill factor of PVs with a SARL and a MARL improved by 33.3% and 54.5%, respectively, because the ARL can be used as the passivation layer. The passivation layer mainly reduces recombination at edge, front and back surface areas [16,17]. Recombination centers with high recombination rates are usually close to the junction (usually a surface or a grain boundary), which will allow carriers to move to this recombination source very quickly and recombine, thus dramatically increasing the recombination current.…”
Section: Methodsmentioning
confidence: 99%
“…Chevtchenko et al have demonstrated reduced reverse leakage current in GaN Schottky diodes passivated ex situ by SiN x or SiO 2 . 10 SiN x layers grown in the III-N metalorganic chemical vapor deposition (MOCVD) chamber (in situ growth) have also been shown to reduce threading dislocation (TD) density when inserted prior to GaN growth. 11,12 Recently, in situ SiN x growth immediately following AlGaN/GaN growth has been demonstrated as well.…”
Section: Introductionmentioning
confidence: 98%